The First Layer: Single-Track Insights into Direct Energy Deposition Processed Cu-Ni Thermoelectric Alloys - Nick Williams; Kyle Snyder; Ian Smith; Anthony Duong; Everett Carpenter; Radhika Barua (Journal of Manufacturing and Materials Processing)
The shift to sustainable energy has accelerated the development of thermoelectric (TE) material for direct heat-to-electricity conversion without batteries or grid reliance. Cu-Ni alloys show promise for high-power, thermally stable TE applications like waste heat recovery and electronics cooling but require thermal conductivity and microstructure optimization. This study investigates additive manufacturing (AM) of Cu-Ni alloys via laser powder-directed energy deposition (L-DED), enabling precise control over deposition parameters. Track geometries were analyzed using linear mass density (ML) and linear heat input (HL), which influence deposition quality and microstructural characteristics. A weighted qualitative process parameter decision matrix was developed to evaluate process conditions systematically. Optimal deposition was achieved with HL < 70 J/mm for ML ~0.016–0.021 g/mm and 98 J/mm < HL < 137 J/mm for ML = 0.026 g/mm, corresponding to an energy-to-mass ratio of ~4000 ± 500 kJ/g. While this study does not directly assess thermoelectric properties, it provides essential first-layer insights into how processing conditions affect track geometry, defect formation, and microstructure—information that is foundational for optimizing multi-layer builds and, ultimately, improving thermoelectric performance. These findings mark a critical step toward predictive process optimization and the accelerated design of Cu-Ni-based thermoelectric materials using AM techniques.